Interaction of some fungal entomopathogens of rice pests with phyllophytic microorganisms of four rice genotypes cultivated in coastal Odisha, India - Sahoo, Biswajit; Dangar, Tushar Kanti (Ecoprint: An International Journal of Ecology, 2016)
Interactions of six entomopathogenic fungi viz. Cordyceps (2 strains), Beauveria (1 strain) and Metarhizium (3 strains) spp. of rice leaf folder (LF, Cnaphalocrocismedinalis) with thephyllophytic (phyllospheric and phylloplanic) bacteria (n=35) and fungi (n=4) isolated at pre-flowering stages of fourcultivated rice (Oryzasativa L.) var. Lalat, Swarna, Swarna-Sub1 and Naveenwere assessed to reveal possibility of intergroup inhibition in the field. Dynamics of the phyllophytic microbes revealed that the phyllospheric bacterial population (3.59 to 4.10 log CFU/cm2) was more than those of the phylloplane (1.56 to 1.75 log CFU/cm2) of different plants. The phyllophytes of the four rice genotypes decreased in the order of Swarna-Sub1 > Swarna > Lalat > Naveen. The fungal pathogens of LF viz. C. brongniartii (TF6 and TF6-1A), B.bassiana (TF6-1B) and M. anisopliae (TF19, TF19- 3A and TF19-3B) were not inhibited by any of the phyllophytic organisms which proved that they can be applied on the canopy of the rice plants to control the pests. ECOPRINT 22: 75-84, 2015